2020
DOI: 10.1111/hiv.13021
|View full text |Cite
|
Sign up to set email alerts
|

The role of CD8 T cells in controlling HIV beyond the antigen‐specific face

Abstract: Objectives Understanding the determinants of HIV immune control is important for seeking viable HIV prevention, treatment and curative strategies. The antigen‐specific roles of CD8 T cells in controlling primary HIV infection have been well documented, but their abilities to control the latent HIV reservoir is less well studied. Methods The scientific literature on this issue was searched on PubMed. Results Recent reports have demonstrated that CD8 T cells are also involved in the control of viral replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Although CTLs can inhibit defective proviruses, their ability to control intact proviruses is limited. [ 54 ] The effectiveness of CD8 + T cells in restraining HIV reservoirs remains unclear. In addition, CTL-mediated HIV eradication faces some obstacles, such as HIV immune escape, CD8 + T cell exhaustion, CD8 + T cell compartmentalization and HIV latency.…”
Section: Adaptive Immune Response and Hiv Reservoirmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CTLs can inhibit defective proviruses, their ability to control intact proviruses is limited. [ 54 ] The effectiveness of CD8 + T cells in restraining HIV reservoirs remains unclear. In addition, CTL-mediated HIV eradication faces some obstacles, such as HIV immune escape, CD8 + T cell exhaustion, CD8 + T cell compartmentalization and HIV latency.…”
Section: Adaptive Immune Response and Hiv Reservoirmentioning
confidence: 99%
“…The ability of CTLs to effectively recognize and eliminate HIV-infected cells is essential for reducing HIV reservoirs. Although CTLs can inhibit defective proviruses, their ability to control intact proviruses is limited [54] . The effectiveness of CD8 + T cells in restraining HIV reservoirs remains unclear.…”
Section: Adaptive Immune Response and Hiv Reservoirmentioning
confidence: 99%
“…The primary target of HIV infection is CD4+ T cells, resulting in the massive loss of CD4+ T cells during the early stage of infection, especially in the lymphoid tissue that is associated with the gut [67,95,96]. CD8+ T cells are, however, activated as a host immuno-logical response to elicit cytotoxic effects against HIV infection at this acute stage [97][98][99]. Gray et al [100] investigated the patterns of HIV-1-specific T cells at the acute stage of infection using the gamma interferon (IFN-gamma) enzyme-linked immunospot (ELISPOT) assay to measure the level of responses against the HIV-1 proteome.…”
Section: Mechanism Of Viral Control Among Ecs and Ltnps As Derived Fr...mentioning
confidence: 99%
“…Of which, we previously showed that a virtual memory T (T VM ) cells subset, defined by CD44 hi CD122 hi CD49d lo in mice and CD45RA+ killer Ig-like receptors (KIR)+ and/or CD94 natural killer group 2 member A (NKG2A)+ in humans (17,26,27), senses and inhibits the reactivation of HIV-1 reservoir through KIR (28). Thus, T VM cells might represent a bystander CD8+ Tcell subset of interest in terms of constraining the size of HIV-1 reservoirs (29). The clinical relevance and functionality of this subset warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%